J. Baird Callicott, Thinking Like a Planet: The Land Ethic and the Earth Ethic - Crosby, Donald A. (Journal for the Study of Religion, Nature and Culture, 2018)
J. Baird Callicott, Thinking Like a Planet: The Land Ethic and the Earth Ethic (New York: Oxford University Press, 2013), 389pp., 41.95, ISBN: 978-0-19-932489-7.